Pengaruh E-Commerce (Shopee) terhadap Kecenderungan Pembelian Impulsif pada Masyarakat Bulotada’a Barat Kecamatan Sipatana Kota Gorontalo - Malasugi, Mohammad Emod I.; Asnawai, Melan Angriani; Isa, Ramlan Amir (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study was motivated by the growing tendency of impulsive buying among the people of Bulotadaa, driven by the ease of access and aggressive promotion on e-commerce platforms. The increasing use of e-commerce platforms has significantly changed consumer behavior. This research aimed to determine the influence of e-commerce on impulsive buying tendencies in the community of Bulotadaa Barat, Sipatana Subdistrict, Gorontalo City. This research employed a quantitative approach using simple regression analysis with a total of 88 respondents. The validity test results showed that all questionnaire items were valid, and the reliability test using Cronbach’s Alpha yielded a score of 0.632. The findings of the study conclude that there is a significant influence of the independent variable (e-commerce) on the dependent variable (impulsive buying). This is supported by the t-test results showing a significance score of 0.029 < 0.05, indicating that the H₀ is rejected and Hₐ is confirmed. Furthermore, based on the coefficient of determination (r² test) from the Model Summary table, the R-square obtained is 0.484 (48.4%). This means that the independent variable explains 48.4% of the dependent variable, while the remaining 51.6% is explained by other variables not examined in this study.